2022
DOI: 10.1186/s41182-022-00453-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with COVID-19 vaccine acceptance among the general population in Asadabad, Iran: a cross-sectional study

Abstract: Background Vaccination can be an essential protective measure against Coronavirus disease 2019 (COVID-19) if well received by the public. Various factors affect the acceptance or refusal of vaccines. Several waves of COVID-19 caused much death in Iran. This study aimed to evaluate the acceptance of the COVID-19 vaccine in the general population of Asadabad in 2021. Methods In this cross-sectional study, 650 people from the general population of Asa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These results are consistent with other studies that have reported associations between vaccination willingness and factors such as profession type, education level, and marital status [12]. Previous research has suggested that being married, highly educated, experienced, or a doctor is all associated with better perception, attitude, and willingness to take up COVID-19 vaccines [4,9,10,12,16,29,30], which is in line with our findings. It is possible that these demographic characteristics are linked to higher levels of knowledge, responsibility, and concern for family, which may contribute to greater acceptance of vaccines.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with other studies that have reported associations between vaccination willingness and factors such as profession type, education level, and marital status [12]. Previous research has suggested that being married, highly educated, experienced, or a doctor is all associated with better perception, attitude, and willingness to take up COVID-19 vaccines [4,9,10,12,16,29,30], which is in line with our findings. It is possible that these demographic characteristics are linked to higher levels of knowledge, responsibility, and concern for family, which may contribute to greater acceptance of vaccines.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the majority of respondents (62.5%) reported that they would encourage their family and friends to get vaccinated for COVID-19, but this percentage was lower than that reported in a study conducted in Saudi Arabia, in which approximately 92% of respondents recommended that their family receive the COVID-19 vaccine (21). In line with these nding, friends or family members vaccinated for COVID-19 consumed the COVID-19 vaccine at least two times more often than did those who were not vaccinated; however, these ndings are lower than those of studies conducted in Iran, in which the likelihood of receiving the vaccine among people who encouraged their families to receive the vaccine was seven times greater than that among people who were not vaccinated (25). This may be because they might have seen the suffering of their family members due to COVID-19 infection.…”
Section: Discussionmentioning
confidence: 56%
“…25) after running the bivariate logistic regression. Age p(0.025), education status p(0.061),occupation p(0.001), had any chronic disease p(0.145), ever tested for COVID-19 p(0.001), friends or family of member vaccinated for COVID-19 p(0.001), attitude towards COVID-19 vaccine p(0.001), knowledge about COVID-19 vaccine p(0.001), perceived susceptible p(0,001), perceived severe p(0.001), perceived bene t p(0.001), perceived barrier p(0.001), clue to action p(0.001), self-e cacy p(0.001).The following candidate variables were signi cantly related to COVID-19 vaccine use according to bivariate analysis: occupation, ever tested, friends or family members vaccinated for COVID-19, attitude towards COVID-19, perceived susceptibility, perceived bene t, and a clue to action.…”
mentioning
confidence: 99%
“…Consistent findings of extensive research indicate that the decision to vaccinate against COVID-19 is influenced by diverse factors, including sociodemographic characteristics, sociocultural and religious considerations, political perspectives, trust in healthcare professionals and current vaccines, the availability and accessibility of vaccination services, and fear of COVID-19 [ 12 , 14 , 17 19 ]. Studies from Thailand reported a strong association of sociodemographics and health system influencers with the COVID-19 vaccination decision [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%